1996
DOI: 10.1084/jem.184.2.557
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide in Tanzanian children with malaria: inverse relationship between malaria severity and nitric oxide production/nitric oxide synthase type 2 expression.

Abstract: SummaryNitric oxide (NO)-related activity has been shown to be protective against Plasmodium fakiparum in vitro. It has been hypothesized, however, that excess NO production contributes to the pathogenesis of cerebral malaria. The purpose of this study was to compare markers of NO production [urinary and plasma nitrate + nitrite (NO~)], leukocyte-inducible nitric oxide synthase type 2 (NOS2), and plasma TNF-c~ and IL-10 levels with disease severity in 191 Tanzanian children with and without malaria. Urine NO• … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
305
1
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(341 citation statements)
references
References 54 publications
16
305
1
3
Order By: Relevance
“…Most studies to date have associated inducible NO production in the mammalian host with anti-parasitic effects (Rockett et al, 1991, Naotunne et al, 1993, Mellouk et al, 1994, Anstey et al, 1996, Pino et al, 2004, Sharma et al, 2004 as well as with increased inflammatory pathology to the host Cowden, 2003 andRiley et al, 2006). In contrast, two studies have concluded that higher levels of NO in humans (Hobbs et al, 2002) and in mice (Gramaglia et al, 2006) were associated with less severe malaria but no differences in parasitemia levels.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Most studies to date have associated inducible NO production in the mammalian host with anti-parasitic effects (Rockett et al, 1991, Naotunne et al, 1993, Mellouk et al, 1994, Anstey et al, 1996, Pino et al, 2004, Sharma et al, 2004 as well as with increased inflammatory pathology to the host Cowden, 2003 andRiley et al, 2006). In contrast, two studies have concluded that higher levels of NO in humans (Hobbs et al, 2002) and in mice (Gramaglia et al, 2006) were associated with less severe malaria but no differences in parasitemia levels.…”
Section: Resultsmentioning
confidence: 90%
“…Nitric oxide has also been linked to the development of cerebral malaria, the most severe form of human infection, with most studies reporting a positive association between high NO levels and increased pathology in late stage disease (Clark and Cowden 2003). In contrast, Anstey et al, (1996) documented that high NO levels were associated with reduced malaria severity and low parasite density and Hobbs et al, (2002) showed that higher NO production was associated with less severe malaria but with no differences in parasitemia levels. As such, studies of NO levels in human malaria have revealed both protective and pathological effects.…”
Section: Introductionmentioning
confidence: 86%
“…38 However, increased expression of NOS2 in PBMC, and particularly in monocytes, 39 leading to increased NOS2-derived NO synthesis, is associated with protection against clinical disease. 40 It seems therefore too early to establish a definitive causal association between NOS2 polymorphisms and malaria susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Nitric oxide (NO), which has been shown to be produced at higher levels by mononuclear cells in asymptomatic children [96], can suppress the pathogenesis of severe malaria through induction of heme oxygenase-1 (HO-1), CO production, and inhibition of T cell activation [97]. However, conflicting results have questioned the role for NO in mediating tolerance [98].…”
Section: Production Of Anti-inflammatory Moleculesmentioning
confidence: 99%